Comparison of assist/control ventilation with and without volume guarantee in term or near-term infants - Bezirganoğlu, Handan; Okur, Nilüfer; Büyüktiryaki, Mehmet; Oğuz, Şerife Suna; Alyamaç Dizdar, Evrim; Sarı, Fatma Nur (My University, 2024)
Objectives: This study aimed to compare the effects of volume guarantee (VG) combined with assist/control (AC) ventilation to AC alone on hypocarbia episodes and extubation success in infants born at or near term. Methods: In this prospective cohort study, infants >34 weeks of gestation at birth, who were born in our hospital supported by synchronized, time-cycled, pressure limited, assist/control ventilation (AC) or assist-controlled VG mechanical ventilation (AC + VG) were included. After admission, infants received either AC or VG + AC using by Leoni Plus ventilator. The ventilation mode was left to the clinician. In the AC group, peak airway pressure was set clinically. In the VG + AC group, desired tidal volume was set at 5 mL/kg, with the ventilator adjusting peak inspiratory pressure to deliver this volume. The study was completed once the patient extubated. Results: There were 35 patients in each group. Incidence of hypocarbia was lower in the VG + AC compared with AC (%17.1 and 22.8%, respectively) but statistically not significant. Out-of-range partial pressure of carbon dioxide (PCO2) levels were lower in the VG + AC group and it reached borderline statistical significance (p = 0.06). The median extubation time was 70 (42-110) hours in the VG + AC group, 89.5 (48.5-115.5) hours in the AC group, and it did not differ between groups (p = 0.47). Conclusion: We found combining AC and VG ventilation compared with AC ventilation alone yielded similar hypocarbia episodes and extubation time for infants of >34 gestational weeks with borderline significance lower out-of-range PCO2 incidence.
Keywords: Assist Controlled Ventilation; Extubation Success; Hypocarbia; Term Infant; Volume Guarantee